Penentu Spread Bunga Bank Di Indonesia - Kurniawati, Andi (Akademi Akuntasi Effendiharahap, 2022)
This study examined the effect of monitoring power, capital adequacy, inefficiency, liquidity, and bank size on the interest rate spread of banks in Indonesia. The analysis was used linear regression model to estimate the effect of various variables. The result of the study indicates that monitoring power was positively insignificant, capital was positively significant, inefficiency was negatively significant, liquidity was positively significant, and bank size was negatively significant on interest rate spread.